The impact of a repeated sprint training program on performance measures in male field hockey players - Taylor, L.; Jakeman, J. R. (The Journal of Strength and Conditioning Research, 2022)
Sprint interval training (SIT) has been shown to be effective at improving athletic performance in laboratory studies, but the efficacy of SIT programs incorporated into normal training schedules is poorly considered. This study aimed to investigate the impact of a running SIT intervention applied to competitive athletes within a training program and to consider whether an uphill or flat (horizontal) SIT protocol had different effects on performance changes over time. Eighteen male hockey players (mean ± SD: age, 20.7 ± 0.9 years; hockey training experience, 9.9 ± 3.0 years) completed 2 sessions of SIT per week for 8 weeks, with intensity progressively increasing from 6 sprints in week 1 to 12 sprints in week 8. Subjects were randomly allocated to a flat or uphill (6% gradient) training condition (n = 9) and completed 30-m maximal sprint efforts with a 30-second recovery. Performance measures, including squat jump, 30-m sprint speed, and repeated sprint time, all improved significantly (p = 0.05). Squat jump performance improved by 3.84 (d = 0.8) and 3.55 (d = 0.7) in the flat and uphill groups, respectively. Thirty-meter sprint speed improved by 0.06 (d = -0.4) and 0.10 (d = -0.7), and repeated sprint performance also improved, with the fastest of recorded sprints after intervention being 0.06 and 0.04 faster in the flat and uphill groups, respectively. Supplementing a normal hockey training week with SIT can have a positive impact on performance measures in male university hockey players. Furthermore, using an uphill training modality had a small, nonsignificant additional positive effect to some performance adaptations.